Surgical Treatment of Paediatric Thalamic Gliomas—Single-Centre Experience - David Krahulik; Filip Blazek; Matej Halaj; Lumir Hrabalek; Eva Stepanova; Zdenek Pavelka; Marie Rohanova (Brain Sciences, 2024)
The surgical treatment of paediatric thalamic gliomas has been burdened with high morbidity, and these lesions were often considered inoperable. With new approaches and intraoperative technologies, we can remove tumours once deemed inoperable. In our single centre, we have operated on 11 paediatric patients over the course of 8 years. We have performed eight GTR resections and three intended subtotal resections. The postoperative neurological deficit ranged from mild to very severe for motor weakness and none to severe for aphasia after surgery, with all of the patients improving at 3-month follow-up. Radicality in the surgical approach to thalamic gliomas in children has shown significant benefits when compared to more conservative approaches. For children with LGGs, extensive surgical resection is associated with improved prognosis and longer progression-free survival. However, it does not yield the same proportional benefit for HGGs due to its aggressive nature and worse outlook.